ALAT TEPAT GUNA UNTUK PEMBUATAN LOGO PADA PROSES PEMBUATAN SEPATU UNTUK INDUSTRI KECIL - Aris Budianto (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2013)
Shoes in addition to those known from the model are also of the designation. Shoes are known not only as described above, but because of the following trademark or logo. The logo can be made by embossed. The authors in this study chose the title "Appropriate Tool System For Making Logo Shoe Molding Process For Small Industries". This study uses a leather material will be varied to variations in skin type, pressure length, and pressure temperature. This type of leather used vegetable leather and leather box. Press length made two kinds of 10 seconds and 20 seconds, while the pressure temperature made three kinds, namely the scale of 100, 200 and 300. Each treatment to obtain a set of four samples of 48 kinds of samples to test the tool pressure. In this study, the longer pressure results are seen more clearly, as well as the temperature, the higher the temperature, the more clearly also embosse result. The optimum results emboss, obtained at position 300 temperature scales and pressure length at 20 seconds on both kinds of leather used.